2004
DOI: 10.1002/elan.200302879
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Recognition of Amino Acid by Differential Pulse Voltammetry in Molecularly Imprinted Monolayers Assembled on Au Electrodes

Abstract: An electrochemical sensor based on l-cysteine SAM imprinted by l-serine has been developed for the detection of lserine. The sensor shows some entantioselectivity toward l-serine and a stable response establishes within 5 min. The peak current intensity of potassium ferricyanide quantified by differential pulse voltammetry (DPV) decreased linearly with increasing l-serine concentration from 10 to 100 mM with a gradient of 20.91 nA mM À1. The detection limit was 4.32 mM. The coefficient of enantiometric selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Piletsky et al [148] prepared a self-assembled monolayer (SAM) of hexadecyl mercaptan on a gold electrode in the presence of a cholesterol template and used the imprinted SAM to measure the cholesterol concentration using potassium ferricyanide as the electrochemical probe. The use of an organic SAM to create molecular recognition sites on gold electrodes for developing various chemical sensors was reported by several laboratories [149][150][151][152][153][154]. Using nanoparticles as scaffolds, Boal and Rotello [155] assembled multivalent binding sites for flavin on gold colloids, where diaminopyridine-and pyrene-functionalized thiols were chosen as building blocks.…”
Section: Interfacing the Mips With A Transducermentioning
confidence: 99%
“…Piletsky et al [148] prepared a self-assembled monolayer (SAM) of hexadecyl mercaptan on a gold electrode in the presence of a cholesterol template and used the imprinted SAM to measure the cholesterol concentration using potassium ferricyanide as the electrochemical probe. The use of an organic SAM to create molecular recognition sites on gold electrodes for developing various chemical sensors was reported by several laboratories [149][150][151][152][153][154]. Using nanoparticles as scaffolds, Boal and Rotello [155] assembled multivalent binding sites for flavin on gold colloids, where diaminopyridine-and pyrene-functionalized thiols were chosen as building blocks.…”
Section: Interfacing the Mips With A Transducermentioning
confidence: 99%
“…Huan et al . () reported the formation of a MIM of l ‐serine and d ‐serine in a l ‐cysteine monolayer on gold. The imprinted monolayer was formed by immersing the clean gold surface in 100 mM HCl solution with 0.2 M l ‐cysteine and 0.1 M l ‐serine for 18 h. The template, l ‐serine, was removed by washing the gold monolayer surface using a 10 mM HCl solution followed by rinsing with water.…”
Section: Monolayer Templatingmentioning
confidence: 99%
“…After removal of the template, the researchers again used the ferrocyanide-ferricyanide redox electrochemical reaction to detect cholesterol in the range of 66 and 700nM; however, control experiments with analogous molecules were not reported. Huan et al (2004) reported the formation of a MIM of L-serine and D-serine in a L-cysteine monolayer on gold. The imprinted monolayer was formed by immersing the clean gold surface in 100mM HCl solution with 0.2M L-cysteine and 0.1M L-serine for 18h.…”
Section: Molecularly Imprinted Monolayers On Gold Surfacesmentioning
confidence: 99%
“…In recent years, the molecular self-assembly method has been used to modify metal surfaces for specific electrochemical applications such as templates for metal nanoparticle electrodepositions [1][2][3][4][5][6][7][8][9], corrosion inhibition [10][11][12][13][14][15] and electrochemical sensors [16][17][18][19][20][21]. A review of the formation and structure of self-assembly monolayers (SAM) was given by Ulman [22] and Kubota and co-workers [21], who investigated their application as electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%